THE VILLAGE ACCOUNTING KNOWLEDGE AND COMPREHENSION ENHANCEMENT FOR VOCATIONAL HIGH SCHOOL ACCOUNTING TEACHERS IN TULUNGAGUNG - Cipto Wardoyo; Rizky Firmansyah; Slamet Fauzan; Adam Gumilang Rahmawan (Pasundan International of Community Services Journal (PICS-J), 2021)
Considering the various regulations that issued by government such as Act Number 2014 in relation to Villages which contained the Village Government Authorities, Rights, and Obligations as well as The Minister of Home Affairs Regulation (Permendagri) Number 113 Year 2014 concerning Village financial management which included the Guidelines and Stages to avoid Village financial management mistakes and misunderstanding between Village government in its organization. Educational institutions have executed the Village Accounting subjects that will be studied by Vocational High School students in 2018. Thus, it required knowledge and understanding about Village Accounting for Vocational High School Accounting teachers, especially in Tulungagung. In this practice, the researcher presented understanding through lecture and practicum methods using SISKEUDES application in order to generate competent accounting teachers.